Antifungal Photodynamic Activity of Hexyl-Aminolevulinate Ethosomes Against Candida albicans Biofilm - Wang, Yingzhe; Song, Jinru; Zhang, Feiyin; Zeng, Kang; Zhu, Xiaoliang (Frontiers in Microbiology, 2020)
Biofilm formation is responsible for the development of chronic and recurrent Candida albicans infections. The generation of biofilms is commonly accompanied by high resistance to conventional antifungal drugs, which can increase up to 1,000-fold. Fortunately, antimicrobial photodynamic therapy (aPDT) has shown excellent potential to treat biofilm infections. However, the current most commonly used photosensitizer (PS), aminolevulinic acid (ALA), is hydrophilic, unstable, and has low permeability, leading to unsatisfactory effects on biofilm eradication. To solve these problems, more stable lipophilic PSs and more effective permeability carriers could be considered as two effective solutions. Hexyl-aminolevulinate (HAL) has good bioavailability as a PS, and we proved in a previous study that ethosomes (ES), lipid-based nanocarriers, promote percutaneous drug penetration. In our previous study, a HAL-ES system presented superior photodynamic effects compared to those of ALA or HAL alone. Therefore, here, we aim to evaluate the biological effects of HAL-ES-mediated aPDT on C. albicans biofilm. An XTT sodium salt assay showed that aPDT using 0.5% HAL decreased C. albicans biofilm activity by 69.71 ± 0.43%. Moreover, aPDT with 0.5% HAL-ES further decreased biofilm activity by 92.95 ± 0.16% and inhibited growth of 25.71 ± 1.61% within 48 h, mostly via its effect on the hyphae growth, which correlated with a three-fold increase in C. albicans plasma membrane permeabilization. Notably, HAL-ES-mediated aPDT significantly reduced the sessile minimum inhibitory concentration 50 (SMIC50) of fluconazole to <2.0 μg/ml, and the 21-day survival rate of C. albicans biofilm-infected mice increased from 6.7 to 73.3%. It also significantly reduced the drug resistance and in vivo pathogenicity of C. albicans biofilm. These results demonstrate that HAL-ES-mediated aPDT could be an effective therapy for C. albicans biofilm infections; while also serving as a particularly promising effective treatment for cutaneous or mucocutaneous candidiasis and the prevention of progression to systemic candidiasis.